PEUBAH-PEUBAH YANG MEMENGARUHI PEMBELI MENGGUNAKAN GERAI VIRTUAL FESYEN - Verena Winardi Kusumo (Universitas Bunda Mulia, 2018)
E-tailers need to know what are customer‟s preferences to use online shop for fashionableproducts. So the purpose of this research is to describe the impact of independent variables likeperceived-price, word-of-mouth, perceived-site-quality, perceived-vendor-reputation, structuralassurance, brand image, and buyer attitude in using online shop. The sample of the study consist of 180respondents by using purposive sampling method. Primary data will be analyzed by SEM (StructuralEquation Modelling). The results show that buyer attitude is directly affected by perceived-price. Brandimage is affected by perceived-vendor-reputation and structural assurance. Buyer attitude is affected bybrand image. Using online shop variable is affected by buyer attitude. Other result shows that brandimage isn‟t affected by word-of-mouth and perceived-site-quality..Keywords: behavior, price, WOM, quality, reputation, assurance